Sustainable supply chains in a changing climate: Analysis and recommendations - Tapasco Alzate, Jeimar; Bedoya, Maria Eugenia; Valencia Garcia, Jhon Brayan; Díaz, Nilton; Cespedes, Jonathan (2021)
The Sustainable supply Chains in a Changing Climate report series, seeks to increase knowledge of the relationship between climate change impacts and agricultural value chains in Colombia. This report aims to collect results of the evaluation of the potential risk of climate impact in five relevant agricultural value chains in Colombia: Cocoa, Maize, Potato, cattle milk, and beef, and propose potential adaptation measures requires to reduce the vulnerability. (2021-08)